Amino-functionalized Fluorescent Carbon Dots for Chemical Sensing. Issue 19 (26th February 2016) - Dai, Jingjing; Zambrana, Michael; Fidalgo, Maria
ABSTRACT: Quantum dots have been applied in sensing with success, but their use in environmental applications has been questioned due to their heavy metal content. Carbon dots are fluorescent nanoparticles that offer a promising alternative to quantum dots for sensing, due to their low cost, benign fabrication process and negligible environmental impact. Fluorescence sensors are specially suited for detection of nitroaromatic compounds such as 2, 4, 6-trinitrotoluene (TNT) and 2, 4-dinitrotoluene (DNT), since they can quench the emission of excited species. When combined to Molecularly Imprinted Polymers (MIPs), the sensors become specific to the imprinted target molecules. Amino-functionalized carbon dots (CDs) with high photoluminescence were fabricated. The CDs were characterized with respect to their surface charge, surface chemistry, particle size distribution, and photoluminescence properties (PL). A molecularly imprinted polymer with template of DNT was combined with fluorescent carbon dots via a simple covalent reaction. The ability of aqueous DNT to quench amino CDs fluorescence was tested for concentrations in the range of 1mM to 50 mM. It can be concluded that the amino carbon dots can be used in fluorescent-labeled MIP systems and that they provide a feasible method for the detection of DNT, and potentially other nitroaromatic compounds, in environmental water samples.